Tackling CMV in Transplant Recipients: Past, Present, and Future - Tal Schlaeffer-Yosef; Lior Nesher (Infectious Diseases and Therapy)
Abstract Cytomegalovirus (CMV), a beta-herpesvirus capable of maintaining lifelong latency, presents a substantial risk to transplant recipients, resulting in significant morbidity and mortality among both hematopoietic stem cell and solid organ transplantation recipients. Recent advances have shifted management from reactive approaches, such as preemptive therapy, to preventive strategies to reduce active infections and disease burden. Letermovir, a selective CMV terminase inhibitor, has emerged as a critical prophylactic agent in high-risk transplant populations, significantly lowering infection rates and improving survival with fewer adverse effects than older antivirals. Maribavir, a UL97 kinase inhibitor, is another recently approved promising option for treating CMV, especially in patients with ganciclovir-resistant or refractory CMV infections. Despite these achievements, the risk of late-onset CMV infection after prophylaxis discontinuation remains a significant clinical challenge. Current research seeks to refine prophylactic regimens and develop advanced diagnostic tools, notably interferon-gamma release assays that measure CMV-specific T cell responses. These immunologic assays may help clinicians identify individuals capable of controlling CMV replication, thus guiding the safer discontinuation of prophylaxis and reducing unnecessary drug exposure. Conversely, patients lacking robust immune reconstitution could be targeted for extended prophylaxis or closer follow-up. Looking into the future, ongoing innovations in immune monitoring and antiviral development will likely lead to a more personalized approach to CMV prevention and treatment, optimizing care based on patient-specific risk profiles and immune competence. As this field continues to evolve, integrating novel therapies, improved diagnostics, and immunity-driven protocols holds promise for further reducing CMV-related complications and improving overall outcomes for transplant recipients.